TRADISI KEAGAMAAN PERANTAU BUGIS DI KOTA KUPANG NUSA TENGGARA TIMUR - Mubarak Taswin; Nurman Said; Emily Nur Saidy; Ni’mah Kurnia (Prodi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Filsafat UIN Alauddin Makassar, 2022)
This study tries to describe the ways by which the Bugis migrants in Kupang, Nusa Tenggara Timur, attempt to preserve their Islamic traditions. The implementation of their Islamic traditions covers various activities symbolizing their adherents to both Islam and Bugis culture within a different religious and cultural environment. This study was conducted as descriptive-qualitative research by implementing socio-anthropological approach in order to understand the fundamental reasons lies behind their commitments in maintaining their Islamic traditions as well as their cultural identity as the Bugis. The data of this research were collected mainly through in-depth interview with numbers of the Bugis migrants who have been living and becoming parts of the of Kupang inhabitants. This research shows that all of the Bugis migrants in Kupang have always taken serious efforts to practice their Islamic traditions as the manifestation of their commitments as the Bugis Muslims. The amenability to maintain their Bugis as well as their Islamic traditions have motivated the Bugis migrants in Kupang to practice traditions with regard to important events in Islamic history as well as of individual and family life cycles. These religious-cultural traditions have contributed to enrich the plurality of religious and cultural traditions coloring the heterogeneity of the daily lives of the people of Kupang which in turn can improve the awareness of the importance of mutual understanding among people regardless their religious and cultural differences.